INFORMATIONAL-ANALYTIC MODEL OF REGIONAL PROJECT PORTFOLIO FORMING - I. A. Osaulenko (Системный анализ и прикладная информатика, 2016)
The article is devoted to the problem of regional project portfolio management in context of interaction of the regional development’s motive forces interaction. The features of innovation development on the regional level and their influence on the portfolio forming process considered. An existing approaches for portfolio modelling and formal criterion of the projects selection analyzed. At the same time the organization of key subjects of regional development interaction described. The aim of the article is investigation of informational aspects of project selection in process of the main development’s motive forces interaction and analytic model of portfolio filling validation. At that an inclination of stakeholders to reach a consensus taking into account. The Triple Helix conception using for concrete definition of the functions of the regional development’s motive forces. Asserted, that any component of innovation triad «science–business–government» can be an initiator of regional project, but it need to support two another components. Non-power interaction theory using for investigation of subjects interrelations in process of joint activity proposed. One of the key concept of the theory is information distance. It characterizes inclination of the parties to reach a consensus based on statistics. Projections of information distance onto directions of development axes using for more accurate definition of mutual positions in the all lines of development proposed. Another important parameter of the model which has an influence on the project support is awareness of stakeholders about it. Formalized description of project in the form of fast set of parameters proposes to use for determination of the awareness. The weighting coefficients for each parameter by expert way. Simultaneously the precision of the each parameter setting for all presented projects determines. On the base of appointed values of information distances and awareness amount of each project defines. After the projects ranking filling of the portfolio in the all lines taking into account limits of projects number and available resources occurs.